2022
DOI: 10.1093/jrr/rrac027
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intensity-modulated radiotherapy with the 5-field technique, helical tomotherapy and volumetric modulated arc therapy for localized prostate cancer

Abstract: The outcomes of three methods of intensity-modulated radiation therapy (IMRT) for localized prostate cancer were evaluated. Between 2010 and 2018, 308 D’Amico intermediate- or high-risk patients were treated with 2.2 Gy daily fractions to a total dose of 74.8 Gy in combination with hormonal therapy. Overall, 165 patients were treated with 5-field IMRT using a sliding window technique, 66 were then treated with helical tomotherapy and 77 were treated with volumetric modulated arc therapy (VMAT). The median age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Clinical trial studies have demonstrated that modern radiotherapy techniques, including IMRT, VMAT, and HT, yield superior treatment outcomes for prostate cancer patients in terms of reduced rectal and bladder toxicities compared to the traditional 3D-CRT [33][34][35]. Techniques, such as HT, can produce a conformal dose distribution to the PTV, significantly reducing the irradiated volume of adjacent normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trial studies have demonstrated that modern radiotherapy techniques, including IMRT, VMAT, and HT, yield superior treatment outcomes for prostate cancer patients in terms of reduced rectal and bladder toxicities compared to the traditional 3D-CRT [33][34][35]. Techniques, such as HT, can produce a conformal dose distribution to the PTV, significantly reducing the irradiated volume of adjacent normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Although many other innovative methods like RT combined with immunotherapy [29] made great progress in recent years, challenges like the unclear pathological mechanism for the occurrence of immune-related adverse effects [30] as well as inter-individual variability [31] remain. While different RT technologies like intensity-modulated RT, volumetric modulated arc therapy [32] and helical tomotherapy [33] enhance therapeutic effect, tumor heterogeneity and radioresistance hinder successful cancer treatment. Radiosensitizers, capable of precise radiation targeting and reducing normal tissue toxicity [34] , offer potential solutions to improve RT efficacy.…”
Section: Introductionmentioning
confidence: 99%